O roli pisarza rozważanej w powiązaniu z instytucjami republikańskimi, czyli Germaine de Staël i polityczność literatury - Ciemińska, Joanna (Polityka i Społeczeństwo, 2020)
This study aims to examine the civilizing impact that a writer should possess under a republican government, as expressed in Germiane de Staël’s works of literary and political theory. The redefinition of the art of writing carried out by Staël is analyzed in the context of French history at the turn of the 18th and 19th centuries, as it was an attempt to overcome the intellectual crisis caused by the political and cultural changes of that period. The classical opposition between a writer, a philosopher and an orator appears unproductive, as the free and „philosophical” word specific to the republican regime is engaged in the same emancipative and enlightening transfer of energy through the enthusiasm shared both by its addresser and receiver. Philosophy and liberty form one and find their fullest expression in literary production, which is considered as a parole, a vibrant, active word. Literature gains thus the status of an existential experience that shapes the human consciousness. Therefore the writer-philosopher is both the guarantee and the ‘work’ of a republican regime, the vector of a socio-political change, of liberation and lumières.